THE PERCEIVED IMPACT OF ENGLISH-SPEAKING ZONES ON STUDENTS’ SPEAKING FLUENCY - Fadhil Rasyid, Nur; Haryanto; Ariyani, Amra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study investigated the implementation of English-Speaking Zones and their perceived impact on students’ speaking fluency at Pondok Pesantren Modern IMMIM Putra Makassar. A qualitative descriptive design was employed involving four students and one English teacher selected through purposive sampling. Data were collected through classroom observations and semi-structured interviews and analyzed using the interactive model of Miles and Huberman, consisting of data reduction, data display, and conclusion drawing. The findings revealed that the implementation of the English-Speaking Zones consisted of three interconnected stages: planning, action, and evaluation. The planning stage involved establishing language regulations, designated English-speaking areas, and vocabulary enrichment activities. The action stage emphasized consistent English use through teacher supervision, peer monitoring, and supporting language activities, while the evaluation stage relied on monitoring and corrective feedback, although it had not yet been conducted systematically. Furthermore, the participants perceived that the English-Speaking Zones contributed to the improvement of several aspects of speaking fluency, including speaking speed, smoothness, vocabulary use, pronunciation, and confidence. However, several challenges remained, such as limited vocabulary, fear of making mistakes, hesitation, and inconsistent use of English in certain situations. It can be concluded that the English-Speaking Zones provide a supportive language environment that encourages students to practice English regularly and supports the development of their speaking fluency. These findings suggest that continuous supervision, meaningful communication opportunities, and systematic evaluation are essential to maximize the effectiveness of the program.